‘Imagining' the Rohingya: Navigating Identity, Memory, and Visibility Examining different methods of documenting Rohingya identities, experiences, and lives. - Bose, Sumona (Department of Political Studies, 2024)
On the 25th of August 2017, the Myanmar military, Tatmadaw, launched a systematic orchestration of what the UN described as a ‘textbook example of ethnic cleansing' of the stateless minority group, the Rohingya residing in the Northern Rakhine region of Myanmar. Since August 2017, more than 700 000 Rohingya fled from Myanmar to Bangladesh. Apart from the gross human rights violations they have suffered from decades long persecution, there is a persistent concern over their loss of identity, culture and personhood. This thesis serves as an explanatory investigation of the complex narratives, memories and experiences of Rohingya lives. It emphasises the importance of socio-cultural interventions conducted through multidisciplinary initiatives aimed at mobilising memory work, that are intended to act as a tool for the Rohingya as a means to navigate their identity and memory politics, agency and advocacy. The need for recognition, dignity, and forms of healing through trauma has been instrumental in resisting the cultural destruction they have endured. This thesis focuses on the accessible modes of acknowledgement that enhances the Rohingya community's visibility by sharing their stories, memories and experiences through memory initiatives considering the prevailing context of exile and uncertainty of return or redress. Memorialisation as a sociocultural and cathartic process has been an important tool of healing, awareness, and dialogue for the Rohingya survivors. By focusing on memory initiatives that have grown from Cox's Bazar with active participation from the Rohingya community themselves, this thesis explores the necessary intervention of deconstructing marginalisation as the dominant positionality of the Rohingya identity.